The role of the pharmacist in patient-centered medical home practices: current perspectives - Lewis NJW; Shimp LA; Rockafellow S; Tingen JM; Choe HM; Marcelino MA (Dove Medical Press, 2014)
Nancy JW Lewis,1 Leslie A Shimp,2 Stuart Rockafellow,2 Jeffrey M Tingen,2 Hae Mi Choe,3 Marie A Marcelino21Private consultancy practice, Rochester Hills, MI, USA; 2Clinical, Social and Administrative Department, University of Michigan College of Pharmacy, Ann Arbor, MI, USA; 3Department of Pharmacy Services, University of Michigan Health System, Ann Arbor, MI, USAAbstract: Patient-centered medical homes (PCMHs) are the centerpiece of primary care transformation in the US. They are intended to improve care coordination and communication, enhance health care quality and patient experiences, and lower health care costs by linking patients to a physician-led interdisciplinary health care team. PCMHs are widely supported by health care associations, payers, and employers. Health care accreditation organizations have created performance measures that promote the adoption of PCMH core attributes. Public and private payers are increasingly providing incentives and bonuses related to performance measure status. Evidence-based prescription, medication adherence, medication use coordination, and systems to support medication safety are all necessary components of PCMHs. Pharmacists have unique knowledge and skills that can complement the care provided by other PCMH team members. Their experience in drug therapy assessments, medication therapy management, and population health has documented benefits, both in terms of patient health outcomes and health care costs. Through collaborative care, pharmacists can assist physicians and other prescribers in medication management and thus improve prescriber productivity and patient access to care. Pharmacists are engaged in PCMHs through both employment and contractual arrangements. While some pharmacists serve a unique PCMH, others work within practice networks that serve practices within a geographical area. Financial support for pharmacist-provided services includes university funding, external grant funding, payer reimbursement, and allocation of PCMH incentives and bonus funds. There is growing support for pharmacist integration into PCMHs; however, more convincing cost-effectiveness data, as well as performance measures requiring the unique skills of pharmacists, may be needed before pharmacist-provided PCMH services become more widely adopted. Given the continued evolution of the PCMH model of care, ongoing opportunities exist for pharmacists to create an optimal care model that is suitable for PCMHs and rewarding for their profession.Keywords: pharmacy practice, multidisciplinary care, advanced practice, pharmaceutical care